Effect of drafting on work intensity in classical cross-country skiing - Bilodeau, B.; Roy, B.; Boulay, M. R. (International Journal of Sports Medicine, 1995)
The purpose of this study was to compare the heart rate responses during cross-country skiing as a leading skier, as well as in a drafting situation, three meters behind the leader. Eight male and two female cross-country ski racers, paired for skiing ability, skied a 2 km course (two loops of 1 km) using the diagonal stride and double-poling techniques at a fixed speed (4.75 m.s-1 and 4.45 m.s-1 for males and females respectively) on two different occasions, once as a leading skier, the other as a drafter. A recovery period of 30 minutes was allowed between the two trials. Heart rates (HR) were registered every five seconds during all performances. Results revealed that HR were significantly lower (165 vs 172 beats.min-1) when skiing behind another skier as opposed to leading. Results also revealed that projected frontal areas appeared to influence the effects of drafting such that the HR differences between the leading and the drafting situations were larger for smaller skiers drafting behind larger skiers. These results showed that skiing behind another skier in a classical cross-country ski race would be very advantageous when the situation is encountered and could help racers using this energy saving strategy.